CONSEQUENCE OF COVID-19 PANDEMIC ON SHARE PRICE MOVEMENTS IN CAPITAL MARKET - Iswi Hariyani; Rhama Wisnu Wardhana (UPT Penerbitan Universitas Jember, 2022)
The capital market longing as funding for companies and other institutions (e.g. the government) and for investing activities. The capital market provides a source of spending with a longer-term, which is invested in capital goods to create and multiply the means of production, creating markets and promoting healthy economic activity. The COVID-19 pandemic since March 2020 and its policies, such as the lockdown, have triggered a multidimensional global crisis in various fields, especially in the economic sector. Indonesia composite index or